Food interactions with tyrosine kinase inhibitors used to treat advanced renal cell carcinoma - Sałek-Zań, Agata; Püsküllüoğlu, Mirosława; Syrek-Kaplita, Karolina; Banaś, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2025)
Renal cancer accounts for approximately 4.4% of all malignant tumors worldwide. In the case of tumors limited to the kidney, the primary method of treatment is surgery. For advanced renal cell carcinoma (RCC), one of the treatment methods is targeted therapy aimed at molecular targets via tyrosine kinase inhibitors (TKIs). These drugs are administered orally, significantly improving the comfort of patients. However, for a drug administered in oral form to produce the intended effect in the body, it must undergo many transformations during which it interacts with various chemical compounds. These include other medications taken by the patient and those derived from food. As a result of these interactions, at each stage of the drug’s transformation, there may be interactions between that drug and these substances. Information about possible drug-drug interactions is widely available. In contrast, knowledge about drug-food interactions is a relatively new area of medical research. It has been demonstrated that these interactions can affect not only the increased toxicity of the therapy but also its effectiveness. This study reviews the possible interactions of popular food products with TKIs used in RCC treatment, at different stages of drug metabolism, and the possible mechanisms of these interactions.